Engineering of melanin biopolymer by co-expression of MelC tyrosinase with CYP102G4 monooxygenase: Structural composition understanding by 15 tesla FT-ICR MS analysis - Park, Hyun A.; Yang, Inchan; Choi, Mira; Jang, Kyoung Soon; Jung, Ji Chul; Choi, Kwon Young (Biochemical Engineering Journal, 2020)
In this study, a novel melanin pigment was synthesized by Escherichia coli cells co-expressing tyrosinase (MelC) and cytochrome P450 monooxygenase (CYP102G4) enzymes simultaneously. The CYP102G4 catalyzes indole C3-specific hydroxylation and generates 3-hydroxyindole (indoxyl) and 3-oxoindole. Additional supply of indole derivatives leads to much darker melanin pigmentation with higher yields (3.4 g/L) of synthesized CYP-Melanin, which showed interesting morphological and electrochemical properties. To understand the correlation between its chemical structure and functions, FT-IRand SEM analysis were attempted. Following 15 T FT-ICR mass spectrometry analysis provided information on the chemical and molecular compositions, characteristics of the synthetic melanins, evidence of higher nitrogen content, and higher degree of unsaturation in the CYP-Melanin structure. Besides, electrical conductivity of CYP-Melanin was determined by cyclic voltammetry (CV) analysis to investigate the feasibility for the application of CYP-Melanin as electrical materials.
Keywords: 15T FT-ICR; CYP102G4; Degree of unsaturations; Electrical conductivity; Escherichia coli cells; FT-ICR mass spectrometry; Indole; MelC; 15T FT-ICR; CYP102G4; Indole; Melanin; MelC; Novel melanin